LITERATURE REVIEW: Pengaruh Resistance ExerciseDengan Elastic Band Untuk Ekstremitas BawahTerhadap Muscle Strength Pada Lansia - Rafa Hanifah Zalfa (2020)
Muscle strength is a term that refers to the ability of contractile networks to produce resultant stresses and forces based on muscle requirements. If you get older then decreased muscle strength. Therefore, efforts must be made to maintain muscle strength, one of which is exercising in the form of resistance exercise using elastic bands. Benefits of resistance training using elastic bands is to increase functional independence and reduce the risk of disease in old age. The purpose of this study was to determine the effect of resistance exercise using elasticband on muscle strength in the elderly. This research method is a Literature Review conducted by collecting from various literature sources. After analyzing, summarizing, synthesizing and comparing shows that there is a significant effect between Resistance Exercise and Elastic Band on muscle strength with the finding of statistical test data p value is <0.005 and there is a strengthening in type II B muscle fibers.